2013
DOI: 10.4330/wjc.v5.i4.68
|View full text |Cite
|
Sign up to set email alerts
|

From the epicardial adipose tissue to vulnerable coronary plaques

Abstract: Thin cap fibroatheromas (TCFAs) are thought to be the most common underlying substrate in patients suffering acute coronary thrombotic events. Recently, an interesting association between TCFAs and a particular depot of visceral fat called epicardial adipose tissue (EAT) has been suggested. In this article, we discuss some basic and clinical aspects of this association and then briefly review some of the pathophysiological characteristics attributed to EAT that explain why this particular depot of fat has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…Low-density lipoprotein (LDL) cholesterol level and EAT volume were independently associated with the percentage of necrotic plaque tissue. These findings are consistent with previous reports [41] . Moreover, EAT is associated also with microvascular dysfunction in the absence of obstructive CAD.…”
Section: Adipose Tissue Depotssupporting
confidence: 83%
“…Low-density lipoprotein (LDL) cholesterol level and EAT volume were independently associated with the percentage of necrotic plaque tissue. These findings are consistent with previous reports [41] . Moreover, EAT is associated also with microvascular dysfunction in the absence of obstructive CAD.…”
Section: Adipose Tissue Depotssupporting
confidence: 83%
“…Human eAT has also been the focus of significant clinical attention, where using various imaging modalities, multiple studies have indicated that an increase in eAT mass and volume associates with the incidence and occurrence of CAD 1 , 2 , and can even serve as a predictor of future coronary events independent of BMI 6 , 8 , 13 , 34 , 35 . However, a number of such studies do not segregate between eAT and the fat lying outside the pericardium i .…”
Section: Discussionmentioning
confidence: 99%
“…The plaque rupture arises in the fibrous layer, which is usually thin and heavily infiltrated by macrophages, which are responsible for maintaining a proinflammatory state of the underlying tissue. Furthermore, EAT secretion of TNF- α , IL-1, and MCP-1 stimulates macrophages and induces apoptosis of vascular smooth muscle cells [ 143 , 144 ]; both events might contribute to weakening of the fibrous layer and subsequent cleavage of the plate. However, the precise mechanisms by which the breaking of the plaque occurs have not yet been fully understood [ 144 ].…”
Section: Epicardial Fat In Clinical Practicementioning
confidence: 99%